Nevelési modellek a Példabeszédek könyvében - MOLNÁR, János (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2017)
Education Models in the Book of Proverbs. The study draws up, describes and presents education models demonstrating the book's pedagogical topicality in the present pedagogical activity. The study also treats issues of history of literature, authorship and genesis period as well as issues regarding the origin of the collection found in the book. It details the notion of Hebrew wisdom, the activity of the wise who teach, respectively the initial phases of the subsequently funded schools. The study specifies and presents five education models: nursing, guiding, ruling, supporting self-development and social sensitivity. The author emphasizes and illustrates the pedagogical topicality of the book.